2020
DOI: 10.1101/2020.07.09.194670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large genetic diversity and strong positive selection in F-box and GPCR genes among the wild isolates ofCaenorhabditis elegans

Abstract: The F-box and chemosensory GPCR (csGPCR) gene families are greatly expanded in nematodes, including the model organism Caenorhabditis elegans, compared to insects and vertebrates. However, the intraspecific evolution of these two gene families in nematodes remain unexamined. In this study, we analysed the genomic sequences of 330 recently sequenced wild isolates of C. elegans using a range of population genetics approaches. We found that F-box and csGPCR genes, especially the Srw family csGPCRs, showed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…9 Chemosensory GPCRs display high sequence divergence and are under strong positive selection in wild C. elegans isolates, and we observe these patterns also for nhr genes (Figure S1A; Table S1). 10 Strikingly, we find a tight correlation between the expansion of nhr genes and GPCR-encoding genes (Figure 1A), a correlation that cannot be explained by the evolutionary relationship of these nematode species or their genome sequence assembly quality (Figures S1B and S1C). While other large nematode transcription factor families (e.g., homeobox genes or C2H2 zinc fingers) also vary in size (Data S1A), the size variation for these transcription factor families does not correlate with the expansion of nhr or gpcr genes (Figure S1D).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…9 Chemosensory GPCRs display high sequence divergence and are under strong positive selection in wild C. elegans isolates, and we observe these patterns also for nhr genes (Figure S1A; Table S1). 10 Strikingly, we find a tight correlation between the expansion of nhr genes and GPCR-encoding genes (Figure 1A), a correlation that cannot be explained by the evolutionary relationship of these nematode species or their genome sequence assembly quality (Figures S1B and S1C). While other large nematode transcription factor families (e.g., homeobox genes or C2H2 zinc fingers) also vary in size (Data S1A), the size variation for these transcription factor families does not correlate with the expansion of nhr or gpcr genes (Figure S1D).…”
Section: Resultsmentioning
confidence: 87%
“…Nucleotide polymorphism and positive selection Data for nucleotide polymorphism and measures of positive selection for all C. elegans genes were obtained from a recent study. 10 As in the original study, all genes that display high nucleotide polymorphism were identified using a cutoff score of Pi > 0.0025. Similarly, genes that show signs of strong positive selection were identified based on fulfillment of both of the following criteria: (1) Tajima's D score < À2, and (2) Fay and Wu's H value < À20.…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the evolution of STRs in C. elegans , a more informative comparison might come from choosing a reference from strains that avoided selective sweeps and was isolated from regions nearby the species origins. For example, the Hawaiian strain XZ1516, which likely carries the most ancestral genotypes (Crombie et al 2019; Ma et al 2021), has contraction in 66% of the 2,400 pSTRs that showed length variation to the reference STRs. Therefore, STR expansion rather than contraction likely occurred from ancestors to descendants in C. elegans if we consider strains that might reflect the ancestral origin of the species.…”
Section: Discussionmentioning
confidence: 99%
“…F-box proteins involved in protein-protein interactions, such as ubiquitinligase complex formation [34], showed a strong response in all treatments. Though their exact function is unknown, many of the several hundred C. elegans F-box genes show signatures of positive selection in wild isolates, suggesting that selective conditions observed in nature were mimicked in the lab [35]. However, nearly half of the identified genes were uncharacterized in function, despite C. elegans being a major model system.…”
Section: Discussionmentioning
confidence: 99%